An assessment of users' needs of the Don Alejandro A. Roces, Sr. Science-Technology High School Library for the purpose of collection development - Robosa, Karlo Martin M. (School of Library and Information Studies, University of the Philippines Diliman, 2007)
A library's collection is its most important asset. School libraries with an established collection and effective readers' services help reach the schools' objective. In order to make this possible, library services, as well as the library's collection, must be based upon an understanding of the service community and its information needs and wants (Evans, 2000). It is in this light that this study is focused on the users' needs assessment of Don Alejandro A. Roces, Sr. Science-Technology High School Library.